The impact of negative interest rates on bank lending : Evidence from Sweden - Venäläinen, Vilma (My University, 2023)
After the Global financial crisis, new ways of maintaining economic stability have had to be thought of. Central banks have introduced unconventional monetary policy tools aimed at keeping the inflation level at the desired level. One of the unconventional monetary policy tools is negative interest rates which have been used to make it more appealing for banks to issue loans to get the money to circulate in the economy. This should appear in the economy so that the inflation will rise closer to the desired level. Negative interest rates are a relatively new phenomenon as a monetary policy tool. Therefore, there is not a great amount of previous literature available, and the purpose of this thesis is to find out if the loan issuance has increased as a consequence of negative interest rates or not. Results from previous studies have been obtained in both directions, so it is not possible to estimate in advance what results should be obtained from this study in order for those to be in line with previous studies. This thesis observes the impact of negative interest rates on bank lending between the years 2011 and 2019. The sample period includes the time before and after the negative interest rates. The thesis also aims to find out whether high-deposit banks issue more loans during negative interest rates than low-deposit banks. The sample is gathered from Sweden where negative interest rates were introduced as a part of the monetary policy during the year 2015 which is a while after the European Central Bank had first introduced those in 2014. The method used in the empirical research part is the panel data method using fixed-effects model. This method is suitable for this kind of research where evidence is gathered from only one country and therefore it is used in this study. The empirical research of this thesis aims to answer the research question with three different regression models. The results of this research show that the interest rates and loan growth have a negative relationship meaning that when loan growth increases, interest rates are decreasing and vice versa. However, the results were not statistically significant when observing the loan growth of high-deposit banks during the negative interest rates with the help of a dummy-variable. Also, the results were not statistically significant either when a dummy variable was added to the regression to describe the period after negative interest rates. Nonetheless, it can be stated that declining interest rates have had an increasing impact on loan growth in Sweden over the years from 2011 to 2019 but statistically significant conclusions of the loan growth of high-deposit banks and low-deposit banks cannot be made based on this study. Globaalin finanssikriisin jälkeen on jouduttu miettimään uusia keinoja talouden vakauden ylläpitämiseksi. Keskuspankit ovat ottaneet käyttöön epätavanomaisen rahapolitiikan keinoja, joilla on pyritty pitämään inflaatio halutulla tasolla. Negatiiviset korot ovat yksi epätavanomaisen rahapolitiikan keino, joiden tarkoituksena on saada pankit myöntämään enemmän lainaa, jotta raha saataisiin taloudessa kiertoon. Tämän pitäisi näkyä taloudessa niin, että inflaatio nousee lähemmäs tavoiteltua tasoa. Negatiiviset korot ovat vielä suhteellisen uusi ilmiö rahapolitiikan keinona. Näin ollen niistä ei ole vielä tehty valtavia määriä aiempia tutkimuksia, ja siten tämän tutkielman tarkoituksena onkin selvittää, että onko lainananto kasvanut negatiivisten korkojen seurauksena vai ei. Aiemmista tutkimuksista on saatu tuloksia molempiin suuntiin, joten etukäteen ei voida arvioida, että mitä tuloksia tästä tutkielmasta tulisi saada, jotta se olisi linjassa aiempien tutkimusten kanssa. Tässä tutkielmassa tarkastellaan negatiivisten korkojen vaikutusta pankkien lainanantoon vuosien 2011 ja 2019 välisenä aikana, jolloin tutkielma käsittää sekä ajan ennen negatiivisia korkoja että ajan niiden käyttöön ottamisen jälkeen. Tutkimuksessa pyritään myös selvittämään, että antavatko pankit, joilla on paljon talletuksia, enemmän lainoja negatiivisten korkojen aikana kuin pankit, joilla on vähemmän talletuksia. Tutkimuksen kohdemaaksi on valittu Ruotsi, jossa negatiiviset korot esiteltiin osana rahapolitiikkaa vuonna 2015 eli hieman sen jälkeen, kun Euroopan keskuspankki oli ne ensin vuonna 2014 esitellyt. Empiirinen tutkimus toteutetaan paneelidataa käyttäen kiinteiden vaikutusten mallin avulla. Kyseinen menetelmä soveltuu hyvin tämän tyyppisen aineiston tutkimiseen, sillä tutkimuksen kohteena on vain yksi maa, jonka vuoksi tämä menetelmä on valittu käytettäväksi tutkielmassa. Empiirisessä tutkimuksessa tässä tutkielmassa tutkimuskysymykseen pyritään vastaamaan kolmen eri regressiomallin avulla. Tutkimus ja sen tulokset osoittavat, että koroilla ja lainan kasvulla on negatiivinen suhde. Tämä tarkoittaa sitä, että kun lainojen määrä kasvaa, niin korot laskevat. Sama pätee toiseen suuntaan. Tulokset eivät olleet tilastollisesti merkitseviä, kun tarkastellaan korkean talletusasteen pankkien lainanantoa negatiivisten korkojen aikana dummy-muuttujan avulla eikä silloin, kun regressiomalliin lisättiin dummy-muuttuja kuvaamaan negatiivisten korkojen aikaa. Voidaan siis todeta, että laskevilla koroilla on ollut kasvava vaikutus pankkien lainanantoon Ruotsissa vuosien 2011 ja 2019 välisenä aikana, mutta korkean ja matalan talletusasteen pankkien lainanannosta ei voida tehdä tilastollisesti merkitseviä johtopäätöksiä tämän tutkimuksen perusteella.
Keywords: monetary policy; central banks; lending; interest (economics); fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance